The use of contraceptive methods and factors related to the pregnancy planning among mothers - Marcela de Oliveira Alves; Bibiane Dias Miranda Parreira; Flavia Aparecida Dias; Lorena Campos Mendes; Thaís Cristina Elias; Sueli da Silva Riul (Universidade Federal de Santa Maria, 2016)
Aim: to describe the use of contraceptive methods and the factors related to the planning of last pregnancy among mothers. Method: quantitative study, with 100 women admitted to a university hospital from the countryside of of Minas Gerais. Data were collected through structured instrument, from July to August 2012. For data analysis descriptive and chi-square test statistic was used. Results: all mothers who planned their pregnancy were married or living in a common-law-marriage; among those who did not plan 68.1% were married, and 30.6% single (p <0.001). Most mothers (59%) used a contraceptive method before their last pregnancy, with a prevalence of combined monthly injectables (67.9%). No significant differences were observed between pregnancy planning and other variables. Final thoughts: it is necessary to prepare health professionals and outreach programs to guide and ensure the right of women to choose the optimal time to procriate